Design of Steel Footbridges for Unpredictive Loadings by STAAD Pro: LRFD vs. ASD for Cost Saving - Naeem, Armghan; Muneeb, Muhammad; Yousaf, Asad; Naeem, Muhammad Mohtasham (Computer Assisted Methods in Engineering and Science, 2022)
Steel footbridges are common means of connecting two zones separated by any kind of physical obstruction to the pedestrian crossing. In the last century, they were mostly designed using manual calculations. With the advent of powerful software, the designing process has become more accurate and less time-consuming. In this paper, complete designing process of steel footbridges is conducted using STAAD Pro: a dedicated steel structure design and analysis software, under unpredictive loading, i.e., dead, live, pedestrian, wind and seismic loading. Two design approaches are popular in steel footbridges designing. These are allowable stress design (ASD) and load and resistance factor design (LRFD), and both are compared with the focus on material/cost saving as cost is the major issue in underdeveloped and overpopulated countries. The critical load combination giving a minimum factor of safety for both approaches is also obtained. It is evaluated that the LRFD design approach results in stronger and lighter structures for unpredictive loadings. The factor of safety for ASD is 20% lower than that of LRFD, and thus LRFD provides material/cost savings of about 20% compared to ASD.